The Influence Of Social Media Marketing And Electronic Word Of Mouth On Purchase Decisions At Vill Garden Moderated By Store Atmosphere - Ida Jaya; Raihani Vinada (MINOVa Ditria Jaya, 2025)
This study aims to analyze the influence of social media marketing and Electronic word of mouth on purchase decisions at Vill Garden moderated by store atmosphere. This study uses a quantitative approach with data obtained through a questionnaire distributed to visitors who make purchases directly to Vill Garden Bandar Lampung with a total of 102 respondents. Data analysis includes validity tests, reliability tests, classical assumption tests, and path analysis processed using PLS software. The results show that Purchase Decision (Z) is influenced by Social Media Marketing (X1), Electronic Word of Mouth (X2), and Store Atmosphere (Y), the Store Atmosphere (Y) variable is influenced by Social Media Marketing (X1) and Electronic Word of Mouth (X2). However, Social Media Marketing has no effect on purchase decisions, Electronic Word of Mouth has a significant positive effect on Purchase Decisions, social media marketing directly through Store atmosphere as an intervening variable affects purchase decisions at Vill Garden, Electronic word of mouth indirectly through Store atmosphere as an intervening variable has no effect on purchase decisions at Vill Garden. This research is expected to provide strategic insights for marketers in designing effective marketing strategies for Vill Garden consumers.